Cost Targeting in a Creative Digital Marketing Company - Salam, Retno Reno Fati; Wijayati, Nureni (APSSAI, 2025)
Research aims: This research aims to evaluate cost control and pricing by applying the target costing concept as a method to improve the process of cost determination in a creative digital marketing agency company. Design/Methodology/Approach: This study uses document analysis and semi-structured face-to-face interview techniques. The interviews were conducted with the Chief Executive Officer, Chief Editor, Chief Business Officer, and Chief Operation Officer of the company. Research findings: The findings indicate that the actual cost of sales incurred by the company has consistently exceeded the acceptable threshold. As a result, the gross profit margin target of sixty percent, which is set by the company, cannot be achieved. However, by applying the target costing concept, the company is able to analyze target costs for its projects so that cost control can be managed more effectively. Theoretical contribution/Originality: This research contributes to the development of cost management theory by demonstrating how the target costing method—commonly used in manufacturing industries—can be adapted and applied effectively within the service industry, specifically in the field of digital marketing agencies. Practitioner/Policy implication: The study presents four recommendations to enhance cost control and pricing: 1) Prepare a working paper for applying target costing to each project; 2) Develop standardized rate cards based on output variables for each service category; 3) Standardize the use of direct costs across all projects; and 4) Identify lower-cost alternative activities and improve the efficiency of value-adding processes.